Patient with rapidly evolving neurological disease with neuropathological lesions of Creutzfeldt‐Jakob disease, Lewy body dementia, chronic subcortical vascular encephalopathy and meningothelial meningioma. Issue 2 (16th September 2016) - Vita, Maria Gabriella; Tiple, Dorina; Bizzarro, Alessandra; Ladogana, Anna; Colaizzo, Elisa; Capellari, Sabina; Rossi, Marcello; Parchi, Piero; Masullo, Carlo; Pocchiari, Maurizio
Abstract : We report a case of rapidly evolving neurological disease in a patient with neuropathological lesions of Creutzfeldt‐Jakob disease (CJD), Lewy body dementia (LBD), chronic subcortical vascular encephalopathy and meningothelial meningioma. The coexistence of severe multiple pathologies in a single patient strengthens the need to perform accurate clinical differential diagnoses in rapidly progressive dementias.